Investigation of Digital Light Processing-Based 3D Printing for Optimized Tooling in Automotive and Electronics Sheet Metal Forming - Szabolcs Szalai; Brigitta Fruzsina Szívós; Vivien Nemes; György Szabó; Dmytro Kurhan; Mykola Sysyn; Szabolcs Fischer (Journal of Manufacturing and Materials Processing)
This study addresses the emerging need for efficient and cost-effective solutions in low-volume production by exploring the mechanical performance and industrial feasibility of cutting tools that are fabricated using stereolithography apparatus (SLA) technology. SLA’s high-resolution capabilities make it suitable for creating precise cutting dies, which were tested on aluminum sheets (Al99.5, 0.3 mm, and AlMg3, 1.0 mm) under a 60-ton hydraulic press. Measurements using digital image correlation (DIC) revealed minimal wear and deformation, with tolerances consistently within IT 0.1 mm. The results demonstrated that SLA-printed tools perform comparably to conventional metal tools in cutting and bending operations, achieving similar surface quality and edge precision while significantly reducing the production time and cost. Despite some limitations in wear resistance, the findings highlight SLA technology’s potential for rapid prototyping and short-run manufacturing in the automotive and electronics sectors. This research fills a critical gap in understanding SLA-based tooling applications, offering insights into process optimization to enhance tool durability and broaden material compatibility. These advancements position SLA technology as a transformative tool-making technology for flexible manufacturing.